Blood Neutrophil-to-Lymphocyte Ratio Predicts Survival in Patients with Colorectal Liver Metastases Treated with Systemic Chemotherapy - Kishi, Yoji (2009)
Background Whether neutrophil-to-lymphocyte ratio (NLR) predicts survival of patients with colorectal liver metastases (CLM) treated with systemic chemotherapy remains unclear. Methods Clinicopathologic data were reviewed for patients with CLM treated with chemotherapy and resection (n = 200) or chemotherapy only (n = 90). Univariate and multivariate analyses for prognostic factors were performed. In the resection group, whether chemotherapy normalizes high NLR and the effect of NLR normalization on survival were evaluated. Results In the resection group, patients with preoperative NLR > 5 had a worse 5-year survival rate than patients with NLR ≤ 5 (19% vs. 43%; P = 0.009), and NLR > 5 was the only independent preoperative predictor of worse survival (P = 0.016; hazard ratio [HR] = 2.22; 95% confidence interval [95% CI], 1.16–4.25). In the nonresection group, patients with prechemotherapy NLR > 5 had a worse 3-year survival rate than patients with NLR ≤ 5 (0% vs. 23%; P = 0.0002), and NLR > 5 was the only independent predictor of worse survival (P = 0.001; HR = 2.91; 95% CI, 1.54–5.50). In the resection group, chemotherapy normalized high NLR in 17 of 25 patients, and these 17 patients had better survival than the 8 patients with high NLR both before chemotherapy and before surgery (P = 0.021). Conclusion NLR independently predicts survival in patients with CLM treated with chemotherapy followed by resection or chemotherapy only. When chemotherapy normalizes high NLR, improved survival is expected.